Investigation of residual stress and optimization of welding process parameters to decrease tensile residual stress in the flash butt welded UIC60 rail - Ghazanfari, Mohsen; Hosseini Tehrani, Parisa (Mechanics based design of structures and machines, 2022)
In this task, a numerical study is utilized to determine the residual stress of the flash butt joint in the UIC60 rail. To accurately predict critical locations of tensile residual stress, the influence of phase transformation is considered in the simulation. To reduce the possibility of failure in the welded rail, the most effective parameters of the flash butt welding during and after the process are optimized to decrease critical tensile residual stresses in the weldment. To this end, a coupled procedure by considering the imperialist competitive algorithm (ICA) in Matlab and process modeling in the Python code of Abaqus software is performed. In this procedure, time duration and heat input at each step and upsetting force are considered as welding machine parameters, and the cooling rate is assumed as post welding factor. Using the effectiveness of the ICA method, in nonlinear and huge multi parameters and steps problems, the optimum values of considered factors in terms of reducing the tensile residual stress in butt joint are obtained. The optimum values and effectiveness of each controlling parameter on the maximum and the pattern of tensile residual stress to diminish the failure of the butt welded rail under service loads are discussed.